Palliative Care Knowledge and Characteristics in Caregivers of Chronically Ill Children. Issue 6 (December 2020) - Johnston, Emily E.; Currie, Erin R.; Chen, Yanjun; Kent, Erin E.; Ornstein, Katherine A.; Bhatia, Smita; Dionne-Odom, J. Nicholas; Rosenberg, Abby R.
Abstract : There is a growing population of children with complex chronic conditions (CCCs) whose caregivers would benefit from palliative care (PC). However, little is known about caregivers' PC awareness. We aimed to describe PC awareness among caregivers of children with CCCs and identify factors associated with lack of PC awareness. We used the National Cancer Institute's national Health Information National Trends Survey 2018 data to determine the percentage of caregivers of ill children who have PC awareness. After matching, caregiver PC awareness was compared with that of (1) the general survey population, (2) other caregivers, and (3) caregivers not caring for children. We used multivariable regression to determine factors associated with lack of PC awareness. Of 131 caregivers, 60% had "never heard of" PC. Caregivers of children were no more likely to have heard of PC than the general survey population ( P = .76), noncaregivers ( P = .97), or caregivers of nonchildren ( P = .13). Caregivers younger than 40 years and without a college degree were less likely to have PC awareness than their peers. Most caregivers of ill children have no PC awareness, with no more PC awareness than the general population. Nurses caring for children with CCCs can help educate families and other health care team members about PC.